The Effects of COVID-19 on Informal Traders in Undesignated Spaces - Emmanuel Ndhlovu; David Mhlanga (Emerging Science Journal, 2023)
The literature on COVID-19 impacts overlooks the pandemic’ impact on informal traders who operate in undesignated public spaces. While studies on the impact of COVID-19 on informal traders exist, there remains little focus on how the socio-economic livelihood activities of informal traders in undesignated public spaces, such as parks, who rely on both domestic and international tourists as customers, have been impacted. This paper fills this gap by focusing on two case studies of urban public spaces in the city of Tshwane, South Africa. These spaces are Jubilee Square and Magnolia Dell Park. The study is predicated on the spatial triad framework which enables it to interrogate how the restriction on access and utilisation of public spaces during the COVID-19 lockdown impacted on the socio-economic activities of informal traders. It found that informal traders in these two parks were the most vulnerable category of traders during the COVID-19 lockdown and faced huge socio-economic and livelihood challenges. They lost their income sources and had their social networks disrupted. The article proposes social policy interventions in the governance of public spaces as part of an effort to save both lives and livelihoods in the face of a pandemic. Doi: 10.28991/ESJ-2023-SPER-07 Full Text: PDF